2015
DOI: 10.1108/pijpsm-07-2014-0075
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect the arrest decision in domestic violence cases

Abstract: Purpose – The purpose of this paper is to examine domestic violence calls for service data in one Florida county for a two-year period from July 2004 through July 2006. Design/methodology/approach – Data for this study include information gathered on domestic violence calls for service during a two-year period (n=3,200). This secondary data were analyzed by logistic regression to determine statistically significant predictor variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…Encounters between the police and children who are victims of domestic violence take place daily around the world. Research has found that children are important in regard to whether or not the mothers report the abuse (Novisky & Peralta, 2015), and that the presence of children increases the likelihood of an arrest (Tatum & Pence, 2015). Nevertheless, it is an overlooked aspect of domestic violence and an issue seldom if ever given the recognition it deserves.…”
Section: Introductionmentioning
confidence: 99%
“…Encounters between the police and children who are victims of domestic violence take place daily around the world. Research has found that children are important in regard to whether or not the mothers report the abuse (Novisky & Peralta, 2015), and that the presence of children increases the likelihood of an arrest (Tatum & Pence, 2015). Nevertheless, it is an overlooked aspect of domestic violence and an issue seldom if ever given the recognition it deserves.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the tools take time to complete and require information that is not readily available to police or is not easily attainable (Hoyle, 2008;Storey et al, 2014). From a police perspective, training is essential to ensure that police officers are accurately and appropriately implementing risk assessment tools, yet various studies have concluded that training for police officers on IPV generally is limited, let alone training on how to conduct risk assessment within the IPV context (DeJong et al, 2008;Gover et al, 2011;Poon et al, 2014;Robinson et al, 2016;Spivak et al, 2020;Tatum & Pence, 2015). By examining how risk assessment tools are used, guidelines can be implemented to improve their utility (Spivak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of risk assessment tools, police officers used their subjective judgment and experience to assess risk. Police officers most commonly respond to incidents of IPV without a risk assessment tool, instead taking into consideration the characteristics of the incident (Tatum & Pence, 2015;Dawson & Hotton, 2014;Poon et al, 2014;Durfee & Fetzer, 2016;Kane, 1999). These characteristics tend to include situational, offender, and victim factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations